Evaluasi Penerapan Metode Job Order Costing Dalam Penentuan Harga Pokok Produksi (Studi Kasus Pada PT Organ Jaya) - Setiawan, Hendra; Surya, Tarida Marlin; Yunita, Yunita (Jurnal Ilmiah Ranggagading (JIR), 2010)
In a condition of very tight market, the strength of the company is absolutely required to be able to survive. The company can reach this by producing product which have good quality so those products can compete with the imported products. One way for the company to be able to win the market is to keep the basic cost of producing goods down in order to be able to keep the prices of the goods down and the quality of the goods satisfies consumers. Product Cost is the basis for the management to determine the selling price of the product. For the company which produces various sort of productâs according to the order specification like the ones at PT. Organ Jaya, the correct product cost calculation is using job order costing method. By using this method the company can calculate the production costs on each order, because by using this method the production cost on each product can be separated clearly. Hence, cost of goods manufactured can be calculated according to the customer order specification. The purpose of research is to find out and evaluate how the job order costing method is determined to be used at PT. Organ Jaya in the calculation of cost of goods manufactured. The evaluation is conducted to know whether the calculation of cost of goods manufactured in the making of hook and eye tape conducted by PT. Organ Jaya has been reckoned accurately. The research conducted by the writer is in PT. Organ Jaya which is location in Jl. Ashari Jaya II No. 20 Ciawi - Bogor. Information for this research is obtained by interview with management, observation, and reading and also studying books related to the problem. According to the evaluation result the writer has made, it can be concluded that PT. Organ Jaya still has not applied job order costing method yet as a whole. For the direct labor cost and factory overhead cost, PT. Organ Jaya still calculates pursuant to the rate, so that result of calculation makes production cost inefficient and incalculable specifically to the product yielded. By the calculation of cost of goods manufactured matching with job order costing method, it will improve production cost efficiency, initially the percentage of margin profit equalâs 31% increases 39%, This can be reached if the company calculates cost of goods manufactured by using media and method matching with job order costing method, so that profit yielded by company earn more maximal. Keywords : job order costing, cost of goods manufactured